THE IMPACT OF ENTROPY ON THE EFFICIENCY OF EXPRESS COURIER SYSTEMS - Dobrodolac, Momčilo; Lazarević, Dragan; Švadlenka, Libor; Blagojević, Mladenka (Journal of Applied Engineering Science, 2015)
The efficiency of organization depends on the level of entropy. Most often, if the entropy is higher, efficiency is lower, and conversely. The model proposed in this paper involves a measurement of the relative efficiency of courier delivery areas - CDA formed to be served by a courier. A question of forming the CDAs is one of the most important in organizing an express courier system. For measurement purpose we used Data envelopment analysis method - DEA. The obtained results indicated which zones are characterized by the presence of entropy. By further analysis, i.e. by calculation the target values for inefficient CDAs we get the directions about possible points where the changes are needed to achieve an improvement. This was done based on the determination of reference efficient decision making units – DMUs, in this case CDAs. Beside this we ranked all the efficient DMUs. The proposed methodology was tested and verified in the case of express courier system of the Post of Serbia which is called Post Express. The empirical example is based on data collected in observation during 30 working days analyzing six CDAs.